Comparison of Acid Sanitizers on Salmonella Typhimurium Inoculated Commercial Poultry Processing Reuse Water - Micciche, Andrew C.; Feye, Kristina M.; Rubinelli, Peter M.; Lee, Jung Ae; Knueven, Carl J.; Ricke, Steven C. (Frontiers in Sustainable Food Systems, 2019)
When considering the cost associated with producing potable water and the environmental concerns associated with water scarcity, the reuse of processing water has received increasing interest. While water reuse during poultry processing can be environmentally friendly, it also brings potential food safety and cross-contamination concerns, through the reuse of water which may harbor human-host pathogens. Therefore, in order to effectively utilize reuse water systems, to mitigate environmental and cost concerns with water use, antimicrobials must be investigated to reduce bacterial and pathogen load. Currently, peracetic acid (PAA) is commonly used in processing water up to 2,000 ppm but can be corrosive with documented public health concerns. As such, sodium bisulfate (SBS) may be utilized as it has the potential to be an important anti-microbial in poultry processing facilities as seen in its application in the produce industry. In this study, SBS, PAA, and industrial grade PAA (IG-PAA) were evaluated against microbial populations in water reuse systems inoculated with Salmonella Typhimurium. Fresh, untreated processing plant reuse water was collected at the end of a poultry processing shift. The water was utilized within one hour of collection, minimum inhibitory concentrations were established, change in pH was investigated, and plate counts after Salmonella addition were performed. When 3x107 CFU of Salmonella was added to each microcosm, a 4 to 5 log reduction with 200 ppm PAA was observed compared to a total killing observed by 5 minutes of treatment with 1%, 2%, or 3% SBS (P < 0.05). The results of this study indicate that SBS may be an equally effective alternative to PAA for decreasing foodborne pathogen contamination in poultry reuse water.